Music in the Development of Spirituality. An approach to Christianity and Buddhism - Gutiérrez, Ana María ('Ilu. Revista de Ciencias de las Religiones, 2015)
Music can affect the individual in all its physical, mental and spiritual levels. This article focuses on the role that it plays in the development of spiritual and transcendental life. To do this, we will make a historical review of its aesthetic and social development, will address this phenomenon physiologically and present their clinical and social applications. Then and as an example of the concepts of Western and Eastern thought, we shall try to describe how Christianity and Buddhism conceive music in its doctrine. We end with some thoughts on the subject.
Keywords: Music; spirituality; religiosity; Christianity; Buddhism.